Approaching Genetics Through the MHC Lens: Tools and Methods for HLA Research - Douillard, Venceslas; Castelli, Erick C. [UNESP]; Mack, Steven J.; Hollenbach, Jill A.; Gourraud, Pierre-Antoine; Vince, Nicolas; Limou, Sophie (Frontiers, 2021)
The current SARS-CoV-2 pandemic era launched an immediate and broad response of the research community with studies both about the virus and host genetics. Research in genetics investigated HLA association with COVID-19 based on in silico, population, and individual data. However, they were conducted with variable scale and success; convincing results were mostly obtained with broader whole-genome association studies. Here, we propose a technical review of HLA analysis, including basic HLA knowledge as well as available tools and advice. We notably describe recent algorithms to infer and call HLA genotypes from GWAS SNPs and NGS data, respectively, which opens the possibility to investigate HLA from large datasets without a specific initial focus on this region. We thus hope this overview will empower geneticists who were unfamiliar with HLA to run MHC-focused analyses following the footsteps of the Covid-19|HLA & Immunogenetics Consortium.
Keywords: association analysis; HLA; immunogenetics; imputation; Major Histocompatibility Complex (MHC)